1999
DOI: 10.1016/s0006-3495(99)77137-7
|View full text |Cite
|
Sign up to set email alerts
|

K+-Dependent Composite Gating of the Yeast K+ Channel, Tok1

Abstract: TOK1 encodes an outwardly rectifying K(+) channel in the plasma membrane of the budding yeast Saccharomyces cerevisiae. It is capable of dwelling in two kinetically distinct impermeable states, a near-instantaneously activating R state and a set of related delayed activating C states (formerly called C(2) and C(1), respectively). Dwell in the R state is dependent on membrane potential and both internal and external K(+) in a manner consistent with the K(+) electrochemical potential being its determinant, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 26 publications
2
32
0
Order By: Relevance
“…This is the same as that described for K ϩ -selective inwardly rectifying channels in animal cells (16). However, rectification of the inward currents in animal cells results from the chronic obstruction by internal Mg 2ϩ or polyamines, whereas ScTOK1 rectification has been reported to be cation independent and is thought to result from an intrinsic property of the channel (18,24). The attributes of rectification were not investigated for NcTOKA currents, though no differences in the rectification of the outward currents were observed upon removal of the Mg 2ϩ from the extracellular solution in the present study (data not shown).…”
Section: Discussionmentioning
confidence: 51%
“…This is the same as that described for K ϩ -selective inwardly rectifying channels in animal cells (16). However, rectification of the inward currents in animal cells results from the chronic obstruction by internal Mg 2ϩ or polyamines, whereas ScTOK1 rectification has been reported to be cation independent and is thought to result from an intrinsic property of the channel (18,24). The attributes of rectification were not investigated for NcTOKA currents, though no differences in the rectification of the outward currents were observed upon removal of the Mg 2ϩ from the extracellular solution in the present study (data not shown).…”
Section: Discussionmentioning
confidence: 51%
“…2 Conversely, TOK1 (the 2P/8TM outward rectifier) shows weak voltage dependence and sensitivity to potassium (40,42,58). Recently, Loukin and Saimi (59) showed that TOK1, like Kcnk3, visits two kinetically distinct closed states, a nearly open state (whose dwell time depends on membrane potential and potassium reversal potential), and a deeply closed state (responsive on voltage and external potassium). They observed that temperature had a significant effect on activation from the deep closed state but little effect on nearly open state.…”
Section: Time-dependent Changes In Kcnk3 Open Probability Withmentioning
confidence: 99%
“…They observed that temperature had a significant effect on activation from the deep closed state but little effect on nearly open state. They concluded that the deep closed state reflected function of a channel gate, whereas the nearly open state was an effect of ions in the pore (59). A role for permeant ion occupancy of the pore in voltage-dependent gating is well recognized in chloride (60) and potassium chan- Ϫ16 Ϯ 6 Calcium added (2 mM, n ϭ 4) ϩ8 Ϯ 3 Magnesium-free (n ϭ 4) Ϫ10 Ϯ 4 Magnesium added (2 mM, n ϭ 4) ϩ1 Ϯ 5 Calcium-free ϩ EGTA (5 mM, n ϭ 4) ϩ7 Ϯ 1 Calcium and magnesium-free (n ϭ 4) Ϫ12 Ϯ 9 Ultra-pure potassium (100 mM, n ϭ 3) ϩ4 Ϯ 1 PMA (50 nM, n ϭ 9) Ϫ13 Ϯ 4 (10 min); Ϫ46 Ϯ 5 (30 min) Bisindolylmaleimide I (5 M, n ϭ 5) ϩ28 Ϯ 3 (30 min) Bisindolylmaleimide I ϩ PMA (n ϭ 4) ϩ9 Ϯ 2 (30 min) Forskolin (20 M) ϩ IBMX (1 mM, n ϭ 3) Ϫ43 Ϯ 6 H-89 (5 M, n ϭ 4) Ϫ5 Ϯ 2 H-89 ϩ forskolin ϩ IBMX (n ϭ 3) Ϫ46 Ϯ 5 Arachidonic acid (100 M, n ϭ 4) Ϫ74 Ϯ 3 Sodium azide (3 mM, n ϭ 6) Ϫ18 Ϯ 3 Hypoxia (O 2 ϳ5 torr, n ϭ 5) Ϫ19 Ϯ 3 Hyperosmotic (100 mM added NaCl, n ϭ 4) ϩ6 Ϯ 7 Halothane (0.35 mM, 3 MAC, n ϭ 3) ϩ17 Ϯ 2 Chloroform (1.3 mM, 2 MAC, n ϭ 3) Ϫ15 Ϯ 2 a These agents were evaluated in 5 mM external potassium; all others were evaluated in 20 mM potassium solution ("Materials and Methods").…”
Section: Time-dependent Changes In Kcnk3 Open Probability Withmentioning
confidence: 99%
“…It was also found to shut down with low ($5 mM) extracellular K + ([K + ] o ) or low cytosolic pH (pH i ) [4]. Its overall behaviour has been modelled with two closed states, either in parallel with a single open state: C 1 MOMC 2 [8] or in series: C 1 MC 2 MO, in which both transitions depend on [K + ] o , but only the first depends on [K + ] i [25]. This discovery, plus a strong difference in temperature dependence of the two transitions, suggests that C 1 MC 2 could be a conventional gating process at the inner surface of the membrane, whereas C 2 MO is probably a property of the selectivity filter.…”
Section: Introductionmentioning
confidence: 99%